Perceptions of EMR usage by health sciences students in Ghana (Journal of Health Informatics in Africa, 2017)
Background and Purpose: Electronic Medical Records improve healthcare delivery, reduce medical errors and costs among many other benefits. A knowledgeable and willing workforce is an important antecedent to actual EMR use. Students in health training institutions should be educated about these tools in order to encourage adoption in their future workplaces. This study therefore set out to identify factors that could influence perceptions of EMR use among College of Health Science students. Methods: This was a cross-sectional study of students of the College of Health Sciences, University of Ghana. EMR perception was measured on 5 domains using a 5-point Likert scale measured from 1 (Strongly disagree) to 5 (Strongly agree). Chi-square tests examined significant differences in the levels of agreement across the respondents’ background characteristics, experience and knowledge in computing. Means were used to determine ranking of applications/tools thought to be most useful for respondents’ work.Results: The study identified age, school affiliation, type of study, health sector work experience, frequency of computer use and knowledge of eHealth communication techniques as factors influencing students’ perception of autonomy and physician-patient relationship. Again, type of study, frequency of computer use and knowledge of eHealth communication techniques were the factors influencing students’ perception of ease of use, usefulness and attitude of physicians.Conclusions: Findings from this study bring to the fore, the need for inclusion of health informatics curricula in training health professionals. This will ensure easier adoption of EMR technology as the country journeys towards a paperless health care delivery system.